Giving in Europe: the state of research on giving in 20 European countries - Hoolwerf, Barry; Schuyt, Theo (Lenthe Publishers, 2017)
Time and again Europeans have to explain that philanthropy is not an American invention. Although media icons such as the Pledge, the Gates Foundation and the Zuckerberg Initiative seem to overwhelm us, they learned it from Europe", states professor Theo Schuyt, resident of the European Research Network on Philanthropy and founder of the Center for Philanthropic Studies at VU Amsterdam, the Netherlands. 'Giving in Europe' sheds light on the European philanthropic performance. It is an initial attempt to map philanthropy in Europe and presents a first overall estimation of the total philanthropic giving by households, bequests, foundations, corporations and charity lotteries. It also contributes to reframing philanthropy in the mindset of many policymakers and politicians in Europe